Green space is associated with new-onset stroke among Chinese middle-aged and older adults: data from China Health and Retirement Longitudinal Study (CHARLS) - Qiong Lu; Qiong Lu; Cheng Lian; Xinglin Chen; Xinglin Chen (Frontiers in Public Health)
Background and aimsThe relationship between green space and new-onset stroke is inconclusive. This study aimed to investigate the association between green space and stroke risk among Chinese middle-aged and older adults.MethodsData were taken from participants aged ≥45 years in the China Health and Retirement Longitudinal Study (CHARLS). Baseline data were collected in 2011 and new-onset stroke data were gathered during follow-up in 2013, 2015, 2018, and 2020. Multivariate Cox regression models were constructed to investigate the association between green space and stroke risk. Subgroup analysis was also performed.ResultsA total of 13,696 participants with a mean age of 59.3 ± 9.3 years were included. After a mean follow-up duration of 6.32 years, there were 728 stroke events during a total of 86,530 person-years of follow-up. The study found a L-shaped relationship between green space and the risk of new-onset stroke in participants. By using a two-piecewise linear regression model, we calculated that the inflection point for the per capita park green area was 10.61 square meters per person (log-likelihood ratio test p = 0.041). On the left of the inflection point, we observed a negative relationship between green space and the incidence of stroke (HR: 0.89, 95% CI: 0.84–0.94, p = 0.0001). On the right side of the inflection point, however, the relationship tended to be saturated (HR: 0.97, 95% CI: 0.94–1.01, p = 0.2111).ConclusionOur study found that the relationship between green space and the risk of new-onset stroke follows a L-shaped curve. A lower amount of green space is associated with an increased risk of new-onset stroke. These findings require confirmation in future studies.